Measurement of Expected Shortfall, Correlation and Simulation of Stock Return in The Transportation Sector in Asia's Emerging Stock Exchanges Before and After The Covid-19 Pandemic - Eko Nurmaryadi; Dewi Hanggraeni (Quantitative Economics and Management Studies, 2023)
The objective of this research is to analyze the market risks encountered by transportation sector companies listed in emerging Asian market countries, as well as the correlation of risks among these companies. Additionally, the study aims to provide a forecasting simulation for the stock prices over the next 100 days. Historical data on daily stock price changes prior to and following the Covid-19 pandemic are utilized. The research methodology employs a normal GARCH model to assess stock volatility, while market risk is determined using the expected shortfall (ES) approach. The Pearson method is employed to calculate the correlation of risks between companies. The forecasting simulation is conducted using the GARCH(1,1) approach for specification and fitting. The findings of this study reveal that transportation sector issuers have exhibited varied responses to the Covid-19 pandemic based on their specific sub-sectors. The correlation between issuers generally demonstrates low values; however, the stock markets of China and Taiwan display a strong positive correlation within the same sub-sector. Future stock price movements over the next 100 days are anticipated to align with the trend observed during the latter part of 2022.